Schizophrenia and mental retardation in an adult male with a de novo interstitial deletion 9(q32q34.1). - Park, J P (1991)
A 28 year old man with mental retardation and therapeutically controlled schizophrenia was found to have a de novo interstitial deletion in the long arm of a chromosome 9 (46,XY,del(9)(q32q34.1). Additional phenotypic abnormalities included short stature, a short webbed neck with a low posterior hairline, dysmorphic facies, a narrow palate with an inverted V soft palate, and tapered fingers with bilateral short fifth metacarpals. Interstitial deletion of chromosome 9 is a rare finding and we are aware of only one other case involving the q32q34.1 region.